Prenylated benzoylphloroglucinols and biphenyl derivatives from the leaves of Garcinia multiflora Champ1. Issue 95 (15th October 2015) - Fu, Wenwei; Wu, Man; Zhu, Lunlun; Lao, Yuanzhi; Wang, Liping; Tan, Hongsheng; Yuan, Qinghong; Xu, Hongxi
<x xml:space="preserve">Abstract</x> Garcimultiflorone I (2), isolated from the leaves of Garcinia multiflora, exhibits significant inhibitory activity against the human SGC7901 and HCT116 cell lines that targets the cell cycle through apoptosis signaling pathways.